glocal - Grigoryeva, Elena (project baikal, 2021)
The term GLOCAL that appeared only thirty years ago and was taken by us as the theme of this issue, is internally contradictory. The global, relating to the globe as a whole, looks like the opposite to the local, partial. Our paradoxical time, however, fills the term with actual meaning. Humanity is united in a common information space, and none of the corners of the Earth can ignore universal human processes and trends anymore. Globality threatens to erase all local differences, unify and average everything and everyone. Against this background, there is an escalating struggle for vivid and unique local national, cultural and ethnic identities, which can be compared with a tree breaking through the asphalt... The pandemic, which has gripped the world, divides people strictly and sets up many borders and walls. But it also unites them, demonstrating the widest range of local options for responding to a deadly threat. The articles from the theoretical section of this issue are devoted to the analysis of the concept of "glocality".